1997
DOI: 10.1210/jcem.82.2.3751
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Thyrotroph Suppression Determined by Third Generation Thyrotropin Assay in Subacute Thyroiditis Compared to Silent Thyroiditis or Hyperthyroid Graves’ Disease

Abstract: Serum TSH concentrations were determined by both second and third generation assays in three types of thyrotoxicosis associated with subacute thyroiditis, silent thyroiditis, and hyperthyroid Graves' disease at the time of each patient's initial visit to the clinic. Serum TSH concentrations as measured by the second generation assay with an analytical sensitivity of 0.04 mU/L were below the detection limit in every patient. In contrast, serum TSH concentrations as measured by the third generation assay with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…Thus, it is suggested that serum TSH was influenced by the period of thyrotoxicosis in our patients. Although we could find no significant correlation between the serum TSH level and the duration of illness, Ito et al . (1997 ) reported that the serum TSH levels declined with disease duration in patients with subacute thyroiditis.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Thus, it is suggested that serum TSH was influenced by the period of thyrotoxicosis in our patients. Although we could find no significant correlation between the serum TSH level and the duration of illness, Ito et al . (1997 ) reported that the serum TSH levels declined with disease duration in patients with subacute thyroiditis.…”
Section: Discussioncontrasting
confidence: 94%
“…Thyrotoxicosis due to destructive thyroiditis such as subacute thyroiditis and painless thyroiditis is known to be caused by a release of thyroid hormones following destruction of thyroid follicular cells, which has a close relationship with viral infection in the former and thyroid autoimmunity in the latter. Recently, Ito et al . (1997 ) reported that serum TSH concentrations determined by a third‐generation assay in patients with subacute thyroiditis were incompletely suppressed.…”
mentioning
confidence: 99%
“…We found that abnormal laboratory findings, such as elevations of FT4, FT3, Tg, CRP, and aminotransferases, reached their peak levels within 7 days after onset, whereas fully suppressed TSH could be detected later, in agreement with a previous report (18). The duration of elevated FT4 was much longer in SAT than in other types of destructive thyroiditis, including painless thyroiditis and acute suppurative thyroiditis, whereas the duration and levels of liver dysfunction in SAT were similar to those in painless thyroiditis (19,20 …”
Section: Episodesupporting
confidence: 92%
“…Generally, OH had lower TSH levels than SH, consistently seen in all sub‐groups. The level of TSH suppression in patients with GD or thyroiditis may, however, be attributed to the duration of disease and a delayed recovery of the pituitary–thyroid axis . An alternative explanation in GD suggests that TRab may control TSH secretion through an ultra‐short feed‐back loop in the pituitary .…”
Section: Discussionmentioning
confidence: 99%
“…The level of TSH suppression in patients with GD or thyroiditis may, however, be attributed to the duration of disease and a delayed recovery of the pituitarythyroid axis. 30 An alternative explanation in GD suggests that TRab may control TSH secretion through an ultra-short feedback loop in the pituitary. 31 This study suggests also that the degree of thyroid hormone elevation matters for the level of TSH suppression.…”
Section: Discussionmentioning
confidence: 99%